The Effectiveness of Group Guidance with Modelling Techniques and Mind Mapping Techniques to Improve Student's Career Planning - Rodliyatun Dyah Purnawati; Purwati; Paramita Nuraini (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
In mountainous areas, such as in the Pakis sub-district, there are still many students who drop out of junior high school or only elementary school graduates, some even decide to drop out in the middle of the school process. It is a lack of understanding, benefits and goals of learning/schooling for them, a lack of understanding from students and parents regarding their career planning. This study aims to test group guidance services with Modeling and Mind mapping techniques to improve student career planning in one of the junior high schools in the Pakis area. This study uses a quantitative research method of true experiment type, the research design is Pretest-Posttest Comparison Group Design with two treatments. The population in this study were students of class IX-B SMP Negeri 3 Pakis with a sample of 10 people and divided into group 1 (Modelling) and group 2 (Mind Mapping). Collecting data using a questionnaire method with random sampling technique. Data analysis using parametric statistics, namely the Anova Test (Analysis of Variance) with the help of SPSS for windows version 25.0. The results of this study indicate that group guidance services with Modeling techniques and Mind Mapping techniques are effective in improving students' career planning. And the Modeling Technique is more effective in improving students' career planning compared to the Mind Mapping technique. This is evidenced by the difference in the average of the experimental group 1 with a score of 36.6 and the experimental group 2 with a score of 33.6, with an average comparison of 3% and the results of the ANOVA test analysis show a significance of 0.005 < 0.05, the probability results show less than 0.05 then the hypothesis Ha is accepted and Ho is rejected. The results of the study can be concluded that group guidance services with modeling techniques are more influential in improving students' career planning.